Simultaneous study of mechanobiology and calcium dynamics on hESC-derived cardiomyocytes clusters - Caluori, Guido; Pribyl, Jan; Cmiel, Vratislav; Pesl, Martin; Potocnak, Tomas; Provaznik, Ivo; Skladal, Petr; Rotrekl, Vladimir (Journal of molecular recognition, 2019)
Calcium ions act like ubiquitous second messengers in a wide amount of cellular processes. In cardiac myocytes, Ca2+ handling regulates the mechanical contraction necessary to the heart pump function. The field of intracellular and intercellular Ca2+ handling, employing in vitro models of cardiomyocytes, has become a cornerstone to understand the role and adaptation of calcium signalling in healthy and diseased hearts. Comprehensive in vitro systems and cell-based biosensors are powerful tools to enrich and speed up cardiac phenotypic and drug response evaluation. We have implemented a combined setup to measure contractility and calcium waves in human embryonic stem cells-derived cardiomyocyte 3D clusters, obtained from embryoid body differentiation. A combination of atomic force microscopy to monitor cardiac contractility, and sensitive fast scientific complementary metal-oxide-semiconductor camera for epifluorescence video recording, provided correlated signals in real time. To speed up the integrated data processing, we tested several post-processing algorithms, to improve the automatic detection of relevant functional parameters. The validation of our proposed method was assessed by caffeine stimulation (10mM) and detection/characterization of the induced cardiac response. We successfully report the first simultaneous recording of cardiac contractility and calcium waves on the described cardiac 3D models. The drug stimulation confirmed the automatic detection capabilities of the used algorithms, measuring expected physiological response, such as elongation of contraction time and Ca2+ cytosolic persistence, increased calcium basal fluorescence, and transient peaks. These results contribute to the implementation of novel, integrated, high-information, and reliable experimental systems for cardiac models and drug evaluation.
Keywords: vápníková signalizace; biosignals filtering; biofyzika; cardiac differentiation; calcium imaging; embryoid bodies; human stem cell-derived cardiomyocytes; lidé; Myocytes, Cardiac; caffeine; Calcium; fluorescence microscopy; Biophysics; atomic force microscopy; Calcium Signaling; vápník; kardiomyocyty; Humans